Corruption of the Local Leaders in Indonesia: An Expository Study - Hadi, Sadhono; Nurmandi, Achmad; Rahardjo, Trisno; Pribadi, Ulung (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2020)
Corruption in Indonesia takes various forms and involves various parties including the local leaders. The aim of this study is to analyze various forms of bribery involving the heads of regencies/Mayors. This study employs qualitative method and focuses on corruption cases in four regencies namely Bangkalan, Karawang, Tegal and Madiun. The research is supported by the Nvivo12 software package that enable researcher to categorize and homogeneous the enormous data. The study found that there are various types of bribery committed by the heads of regencies that include either direct bribery, levies, forced bribery (extortion), or tribute. The type of bribery depends on the specific conditions of each area. The types of corruptions can also be distinguished into hidden and open corruption. Open corruption refers to corruption that involves local governmental units.